Women expert gamers: portrait of an understudied population - Hébert-Ratté, Roxanne; Dufour, Magali; Martel-Brosseau, Geneviève; El-Baalbaki, Ghassan (Frontiers in Psychology, 2025)
IntroductionVery little is known about women who persist in competitive gaming environments and their unique characteristics. Thus, the current study aims to provide an initial portrait of these women.MethodsA subsample of 128 female gamers, selected from a larger internet survey, completed an online questionnaire assessing sociodemographic factors, gaming experience, motives to play, and mental health variables. Self-reported expert gamers were compared to casuals on these variables. Then, a backward logistic regression allowed to identify the best predictors of being an expert gamer.ResultsExperts reported higher gaming involvement and higher levels of specific gaming motives. Experts also tended to engage in specific game types and to report more positive outcomes than casuals. Finally, gaming involvement, competition motive, self-esteem, and game genre were the best predictors of group membership.DiscussionThis study highlighted several unique characteristics of female expert gamers, suggesting an important role of personal and environmental strengths, gaming involvement, and gender representation.